There are infinitely many solutions to 11x - 99 = 11(x - 9)
If: 11x+25 = 7x+15 then there is only one solution and it is x = -2.5
x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.
If 6x + 10 = 11x , then x=2.
-x^2 - 11x - 30 If you intended -1(x squared), making a quadratic equation, the solutions are -1 and +6.
y = 11x + 5 The slope/gradient of this equation is 11. The slope/gradient can easily been seen in a linear equation: it is simply the co-efficient of x
Equations: 7x-8y = 9 and 11x+3y = -17 Multiply all terms in the 1st equation by 11 and all terms in the 2nd by 7 So: 77x-88y = 99 and 77x+21y = -119 Subtract the 1st equation from the 2nd equation: 109y = -218 => y = -2 Through substitution the solutions are: x = -1 and y = -2
It is: (3x+1)(x-4) when factored with the help of the quadratic equation formula.
If you mean: 3x squared -11x -20 = 0 Then: x = -5 or x = 4/3
If you mean: y = 11x+1 then the y intercept is 1 and the slope is 11
The equation -30 times -10 plus 11X equals -29. This is a math problem.
If you mean y = 11x+2.5 then the slope is 11 and the y intercept is 2.5
Write as an equation with division before subtraction. 5/11x-7=2 5/11x=9 mult both sides by 11x 5=99x 99x=5 x=5/99
9x2+11x-14 = (9x-7)(x+2) when factored with the help of the quadratic equation formula.
x2 + 11x + 24 You want the equation to be in the form (x + a)(x + b), where the two solutions are -a and -b.You know that...ab = 24...and...a + b = 11Note that 8 times 3 is 24, and 8 plus 3 is 11.x2 + 11x + 24 = (x + 3)(x + 8)The two answers are x = -3 and x = -8.
It is a linear equation in a single variable, x.
If you mean y = 11x then the slope is 11
X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2
If you mean: 11x+2y = 34 then y = -10.5x+17 whereas -10.5 is the slope and 17 is the y intercept of a straight line equation
2x + 12/x = 11 (x ≠ 0, eliminate the denominator by multiplying each term of the both sides by x) 2x2 + 12 = 11x (subtract 11x to both sides) 2x2 - 11x + 12 = 0 (2x - 3)(x - 4) = 0 2x - 3 = 0 or x - 4 = 0 x = 3/2 or x = 4 Since x = 3/2 and x = 4 satisfy the equation, they are the solutions of the equation.
If you set your equation to equal 7, then you can move 7 to the other side of the equation, and solve for x. This/these values will always result in 7. e.g. 3x2+11x+6=7 3x2+11x+6-7=7-7 3x2+11x-1=0 Factor using the quadratic formula and solve for x.
6 + 11x - 60 =6 - 60 + 11x = -54 + 11x = 11x -54
That's an invalid equation.